ANALYSIS OF THE REASONS OF BREAKAGES OF RETAYNER OF THE CAMP OF PQF AND SOLUTION OF PROBLEMS - A. V. Chubenko (Литьë и металлургия)
The analysis of the reasons of breakages of the equipment of a retayner of the rolling mill PQF of pipe-rolling shop is made. Breakage of a retayner leads to a stop of all shop of hot rolling of pipes. On the basis of the obtained data the solution allowing to increase reliability and durability of the equipment of a retayner is proposed. The solution assumes change of algorithm of work in the operating programmable logical Simatic S7–400 controler of the rolling mill PQF. Changes concern the control unit of movement of a retayner. Transition from the uniformly acceleration of traffic control of a lath of a retayner to not uniformly accelerated is provided. Thanks to this decision the main reason for breakages of the equipment of a retayner of PQF – mechanical blows in gear connections is minimized. The decision doesn’t assume change of a design of the equipment or introduction to work of additional units. Costs of introduction are minimum.